Three-dimensional porous conductive polymer composite material prepared through 3D printing and 3D printing ink and application thereof
Through the preparation of 3D printing ink of graphene nanosheets and polydimethylsiloxane and other components, combined with five-stage heat treatment, the problem of preparation of 3D printing porous PDMS-based conductive composite materials in the prior art is solved, achieving high efficiency and low cost The preparation of porous composite materials has excellent mechanical properties and electrical conductivity, and is suitable for human health monitoring and other fields.
Patent Information
- Application Number
- CN202411610324.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-17
AI Technical Summary
The existing 3D printing process cannot effectively prepare complete porous PDMS-based conductive composite materials. Traditional preparation methods require a large amount of conductive fillers, resulting in high material cost and reduced flexibility.
Graphene nanosheets are used as conductive fillers, and a uniform dispersion is formed through ultrasonic dispersion and mechanical stirring. Combined with solvents such as polydimethylsiloxane and cyclohexane, 3D printed ink is prepared, and three-dimensional porous conductive is obtained through five-stage heat treatment. Polymer composite materials.
It is realized that the use of less conductive fillers can meet the 3D printing requirements, obtain high viscosity ink, overcome the structural collapse problem caused by the rapid solvent volatility in traditional methods, and obtain porous composite materials with excellent mechanical properties and conductivity, suitable for Piezoresistive sensor applications.
Smart Images

Figure CN119320559A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of conductive composite materials, and in particular relates to a three-dimensional porous conductive polymer composite material prepared by 3D printing, and 3D printing ink and application thereof. Background Art
[0002] Conductive polymer composites are non-metallic conductive materials that combine conductive fillers and polymer matrices. Due to their excellent conductive properties and good process properties of polymer materials, conductive polymer composites have been widely used in electronics, electrical appliances, electromagnetic wave shielding, electrostatic protection and other fields. Commonly used conductive fillers include carbon nanotubes, two-dimensional materials, liquid metals, metal nanoparticles and conductive polymers. Commonly used polymer matrices include polymer resins, thermoplastic elastomers and thermoplastic polymers. The polymer matrix has an important influence on the mechanical properties, conductive properties and process properties of conductive polymer composites. At present, polydimethylsiloxane (PDMS) has been selected as a new generation of practical elastic matrix materials because of its good biocompatibility, good stability, simple preparation, good elasticity and excellent mechanical properties at room temperature.
[0003] The preparation method of conductive polymer composites is one of the key factors affecting their performance. Traditional preparation methods include solution blending, melt blending, etc. The solution blending method is to dissolve the conductive filler and the polymer matrix in an appropriate solvent, and obtain the conductive polymer composite by volatilizing the solvent. The melt blending method is to mix the conductive filler and the polymer matrix at high temperature, and then cool and solidify to obtain the composite material. However, these traditional methods all require the addition of a large amount of conductive fillers to form a complete conductive network, which on the one hand increases the cost of the material and causes a waste of resources; on the other hand, a large number of rigid conductive particles are focused together, which may reduce the flexibility of the material, and porous conductive polymers have become one of the solutions to this problem.
[0004] 3D printing technology is a technology that uses digital model files as the basis, using materials such as powdered metal or plastic to construct objects by printing layer by layer. It can obtain molded parts with high strength and good toughness without injection molding, and can be used to produce porous conductive polymer composite materials. However, due to the low viscosity of PDMS, it is still a difficult process to directly use PDMS as printing ink to 3D print a complete PDMS-based conductive composite material. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a three-dimensional porous conductive polymer composite material prepared by 3D printing and its 3D printing ink and application, aiming to solve the problem that a complete porous PDMS-based conductive composite material cannot be obtained through the existing 3D printing process.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A 3D printing ink, comprising the following components in parts by weight:
[0008] 0.175-1.2 parts of graphene nanosheets, 35-40 parts of polydimethylsiloxane, 10-15 parts of cyclohexane, 45-50 parts of deionized water, and 3.5-4 parts of curing agent.
[0009] Furthermore, the 3D printing ink is prepared by the following method:
[0010] Ultrasonic dispersion of graphene nanosheets in a solvent forms a graphene dispersion, polydimethylsiloxane is added to the graphene dispersion and mechanically stirred and dispersed to obtain a mixed solution, the mixed solution is placed on a heating table, and the solvent is evaporated at 70-80° C. to obtain a precursor; the filling amount of the graphene nanosheets is 0.5-3wt% of the polydimethylsiloxane;
[0011] The precursor, cyclohexane and deionized water are mixed in a weight ratio of (35-40%): (10-15%): (45-50%); a curing agent of 10% by weight of polydimethylsiloxane is added during the mechanical stirring and blending process to obtain a 3D printing ink.
[0012] Furthermore, the solvent is one of tetrahydrofuran, chloroform and dichloromethane; and each 1g of graphene nanosheets is dispersed in 15-20ml of the solvent.
[0013] Further, ultrasonic dispersion was performed for 10-15 min at an ultrasonic power of 750 W and a frequency of 50 Hz; and the solvent was evaporated at 70° C. on a heating table.
[0014] The present invention also proposes a three-dimensional porous conductive polymer composite material prepared by 3D printing, which is prepared by the following method:
[0015] The aforementioned 3D printing ink is printed according to a predetermined structure using a 3D printer to obtain a precursor material, and the precursor material is subjected to five-stage heat treatment to obtain a three-dimensional porous conductive polymer composite material.
[0016] Further, the five-stage heat treatment process is:
[0017] (1) Heating at 48-52°C for 30 minutes;
[0018] (2) heating at 88-92°C for 60 minutes;
[0019] (3) heating at 98-102°C for 90 minutes;
[0020] (4) heating at 118-122°C for 120 minutes;
[0021] (5) Heating at 138-142°C for 360 minutes.
[0022] Furthermore, the five-stage heat treatment is carried out in an oven at normal pressure, and the oven heating rate is 1-5°C / min.
[0023] Furthermore, the three-dimensional porous conductive polymer composite material is in the shape of an elongated strip, with a thickness of 1.8 to 2.0 mm in a naturally stretched state, and its length and width can be adjusted as needed; the three-dimensional porous conductive polymer composite material has a compressive strength of 30 to 40 kPa, a compressive strain rate of 17 to 22%, and an initial conductivity of 0.56 to 0.58 S / cm; when the compressive strain is 10%, the resistance change rate is above 75%.
[0024] Furthermore, the air pressure on the printing nozzle is 0.1-0.3 MPa, the moving speed of the printing nozzle is 5 mm / s, the diameter of the printing nozzle is 0.2 mm, the spacing between the single filaments in the layer is 0.1 mm, and the layer thickness is 0.2 mm.
[0025] The present invention also proposes an application of the three-dimensional porous conductive polymer composite material prepared by 3D printing in a piezoresistive sensor.
[0026] The beneficial effects of the present invention are:
[0027] 1. The conductive filler in the 3D printing ink of the present invention is selected as graphene nanosheets, and the graphene nanosheets are mixed and dispersed more evenly inside the PDMS matrix; and the graphene nanosheets account for 0.16% to 1.33% of the total amount of the 3D printing ink. The 3D printing ink has a higher viscosity by doping with less conductive filler, thereby meeting the requirements of 3D printing.
[0028] 2. The three-dimensional porous conductive polymer composite material prepared by 3D printing of the present invention has five heating processes during the curing process, which overcomes the problem of too fast solvent volatilization caused by the traditional single heat treatment process, resulting in the collapse of the 3D printed structure, and obtains a complete three-dimensional structure with 100% filling density. The porous composite material of the present invention has excellent mechanical properties. When the filling amount of graphene nanosheets is 0.5wt%, the compressive strain rate of the composite material is 21% and the compressive stress is 31.23kPa.
[0029] 3. The three-dimensional porous conductive polymer composite material of the present invention has good electrical conductivity. When the filling amount of graphene nanosheets is 0.5wt%, the conductivity of the composite material in the vertical direction is 0.6S / cm. The composite material exhibits excellent pressure sensing ability. When the filling amount of graphene nanosheets is 0.5wt%, the GF value of the composite material at a compression strain rate of 10% is 9.2, and the resistance change remains stable under 20 compression cycles.
[0030] 4. When the three-dimensional porous conductive polymer composite material of the present invention is applied to a piezoresistive sensor, it can be directly attached to the human neck for voice and swallowing monitoring. The present invention has developed a new structure and preparation process of porous composite conductive materials, and provides a new material structure design method for the preparation of human health monitoring materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0032] Figure 1 This is a side view of Example 1 of the present invention.
[0033] Figure 2 This is a top surface photograph of Example 1 of the present invention.
[0034] Figure 3 For Example 1 of the present invention
[0035] Figure 4 For Example 1 of the present invention
[0036] Figure 5 4 is a comparison chart of the compression strength of the embodiments of the present invention.
[0037] Figure 6 4 is a comparison diagram of the compression strain rates of the embodiments of the present invention.
[0038] Figure 7 4 is a conductivity comparison diagram of the embodiments of the present invention.
[0039] Figure 8 4 is a sensitivity coefficient comparison diagram of an embodiment of the present invention.
[0040] Fig. 9 It is a comparison chart of the compressive strength of Example 1 of the present invention and the comparative example.
[0041] Fig.10 It is a comparison chart of the compression strain rate of Example 1 of the present invention and the comparative example.
[0042] Fig.11 It is a conductivity comparison diagram of Example 1 of the present invention and the comparative example.
[0043] Fig.12 It is a comparison chart of sensitivity coefficients of Example 1 of the present invention and the comparative example.
[0044] Fig.13 Schematic diagram of application status of an embodiment of the present invention. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0046] A 3D printing ink, comprising the following components in parts by weight:
[0047] 0.175-1.2 parts of graphene nanosheets, 35-40 parts of polydimethylsiloxane, 10-15 parts of cyclohexane, 45-50 parts of deionized water, and 3.5-4 parts of curing agent.
[0048] The 3D printing ink is prepared by the following method:
[0049] Ultrasonic dispersion of graphene nanosheets in a solvent forms a graphene dispersion, polydimethylsiloxane is added to the graphene dispersion and mechanically stirred and dispersed to obtain a mixed solution, the mixed solution is placed on a heating table, and the solvent is evaporated at 70-80° C. to obtain a precursor; the filling amount of the graphene nanosheets is 0.5-3wt% of the polydimethylsiloxane;
[0050] The precursor, cyclohexane and deionized water are mixed in a weight ratio of (35-40%): (10-15%): (45-50%); a curing agent of 10% by weight of polydimethylsiloxane is added during the mechanical stirring and blending process to obtain a 3D printing ink.
[0051] Furthermore, the solvent is one of tetrahydrofuran, chloroform and dichloromethane; and each 1g of graphene nanosheets is dispersed in 15-20ml of the solvent.
[0052] Further, ultrasonic dispersion was performed for 10-15 min at an ultrasonic power of 750 W and a frequency of 50 Hz; and the solvent was evaporated at 70° C. on a heating table.
[0053] The present invention also proposes a three-dimensional porous conductive polymer composite material prepared by 3D printing, which is prepared by the following method:
[0054] Using a 3D printer, the aforementioned 3D printing ink is printed according to a predetermined structure to obtain a precursor material, and the precursor material is subjected to five-stage heat treatment to obtain a three-dimensional porous conductive polymer composite material; the precursor material is a black strip printed by 3D, and then the black strip is transferred to the oven for five-stage heat treatment; the five-stage heat treatment process is as follows: (1) heating at 48-52°C (for example, 48°C, 49°C, 49.5°C, 50°C, 51°C, 52°C) for 30 minutes, the purpose of which is to remove cyclohexane; at this time, due to the reduction of solvent, the viscosity of PDMS increases, the fluidity decreases, and a preliminary structure is formed; (2) heating at 88-92°C (for example, 88°C, 89°C, 89.5°C, 90°C, 90.5°C, 91°C, 92°C) for 60 minutes, the purpose of which is to further ensure the removal of cyclohexane, and a small amount of water is evaporated in this process; at this time, the PDMS elastomer undergoes preliminary solidification, so that the shape is maintained while the solvent evaporates, but it is also It is not in a solid state, and PDMS is still a viscous liquid; (3) Heating at 98-102°C (for example, 98°C, 99°C, 99.8°C, 100°C, 101°C, 102°C) for 90 minutes to remove moisture. At this time, PDMS continues to solidify and undergoes a phase transition from liquid to solid. At this stage, the solvent evaporates severely, but the PDMS elastomer state has been formed so the shape can continue to be maintained; (4) Heating at 118-122°C (for example, 118°C, 119°C, 120°C, 121°C, 122°C) for 120 minutes to completely solidify PDMS and completely transform it into a solid structure; (5) Heating at 138-142°C (for example, 138°C, 139°C, 140°C, 141°C, 142°C) for 360 minutes to further remove moisture and ensure that the moisture inside the material is completely removed; at this time, all the solvent evaporates, but PDMS completely becomes a solid structure and its shape is not affected. The material is printed in the shape of a long strip with no other structure inside. After five stages of heat treatment, the solvent inside evaporates and becomes a porous structure.
[0055] The preparation method of the present invention is based on the solution blending method. The cyclohexane and deionized water in the 3D printing ink are used to dilute the PDMS and adjust the viscosity of the printing ink, so that the 3D printing can be directly performed and a porous material can be formed after five-stage heat treatment. The boiling point of cyclohexane is 80.7°C. The purpose of designing the heating in sections (1) and (2) is to allow the cyclohexane and deionized water to evaporate slowly. The slower the solvent evaporates, the more the porous morphology of the PDMS elastomer can be maintained. The difference in boiling points between cyclohexane and deionized water can further slow down the evaporation rate of the solvent.
[0056] When the three-dimensional porous conductive polymer composite material prepared by 3D printing is used as a piezoresistive sensor, the long strip of the three-dimensional porous conductive polymer composite material is cut into suitable lengths before use. Fig.13Photo of the device setup for monitoring swallowing activity in the throat using a three-dimensional porous conductive polymer composite cut into short strips.
[0057] The present invention will be described in detail below in conjunction with examples and comparative examples. The graphene nanosheets in the examples have a thickness of 30-40 nm and a sheet diameter of 3-6 μm, and all chemical raw materials are analytically pure products.
[0058] Example 1
[0059] A three-dimensional porous conductive polymer composite material prepared by 3D printing is prepared by the following method:
[0060] S1 prepares 3D printing ink;
[0061] 2 g of graphene nanosheets were dispersed in 30 ml of tetrahydrofuran solvent, and a graphene dispersion was obtained by ultrasonic dispersion at 50 Hz and 750 W for 10 min; PDMS primer was added to the graphene nanosheet dispersion, and the amount of graphene nanosheets added was 0.5 wt % of the PDMS primer. After mechanical stirring and mixing for 30 minutes, the mixed solution was placed on a heating table, and the solvent was evaporated at 70° C. to obtain a precursor;
[0062] The precursor, cyclohexane and deionized water were mixed in a formula ratio of 40%:10%:50%, and mechanically stirred for 30 minutes, during which 10% of the mass of PDMS curing agent was added to obtain 3D printing ink; the curing agent used was Dow Corning DC-184;
[0063] S2 printing to prepare three-dimensional porous conductive polymer composites;
[0064] The 3D printing ink is degassed using a degassing apparatus and then printed using a commercial 3D printer. The syringe capacity of the printer is 3 mL, the air pressure of the printing nozzle is 0.1-0.3 MPa, the moving speed of the printing nozzle is 5 mm / s, the diameter of the printing nozzle is 0.2 mm, the spacing between the monofilaments in the layer is 0.1 mm, and the layer thickness is 0.2 mm; a precursor material is obtained;
[0065] The 3D printed precursor material was subjected to five temperature treatments: first, heated at 50°C for 30 minutes; then, heated at 90°C for 60 minutes; then, heated at 100°C for 90 minutes; then, heated at 120°C for 120 minutes; and finally, heated at 140°C for 360 minutes to obtain the final three-dimensional porous conductive polymer composite material.
[0066] The 3D printing ink raw material in this embodiment 1 can print a three-dimensional porous conductive polymer composite material of at most 20 mm long×10 mm wide×2 mm high.
[0067] The three-dimensional porous conductive polymer composite material prepared in Example 1 was cut into pieces according to Fig.13 Apply it to the back of the throat. Figure 3 The resistance of the three-dimensional porous conductive polymer composite material of Example 1 changes with throat swallowing. When the volunteer swallowed, the resistance of the conductive composite material decreased by more than 70%. After the swallowing action ended, the resistance returned to the initial value, and the resistance change was stable under 7 swallowing actions. This example proves that the material has strong application potential in the field of human health monitoring as a press-type sensor.
[0068] After testing, the compressive strength of the porous three-dimensional conductive composite material prepared in Example 1 is 31.23 kPa, the compressive strain rate is 21%, the initial conductivity is 0.6 S / cm, and when the compressive strain is 10%, the resistance change rate is 92%, and the sensitivity coefficient is 9.2. Figure 4 As shown, 30 compression-release cycles were performed at a compression strain rate of 5%, and the relative resistance change retention rate was stable, indicating that the composite material obtained in this embodiment has good mechanical properties and compression sensing performance.
[0069] Example 2
[0070] The difference between this embodiment and embodiment 1 is that in step S1, acetone is selected as the dispersing solvent for graphene nanosheets, and other operations are the same as those in embodiment 1.
[0071] After testing, the three-dimensional porous conductive polymer composite material prepared in this embodiment has a compressive strength of 31.44 kPa, a compressive strain rate of 20.8%, an initial conductivity of 0.62 S / cm, a resistance change rate of 89% when the compressive strain is 10%, and a sensitivity coefficient of 8.9. It has good mechanical properties and pressure sensing performance.
[0072] Example 3
[0073] The difference between this embodiment and embodiment 1 is that in step S1, the mixing ratio of the 3D printing ink precursor, cyclohexane and deionized water is 45%:10%:45%, and the other operations are the same as those in embodiment 1.
[0074] After testing, the three-dimensional porous conductive polymer composite material prepared in this embodiment has a compressive strength of 32.4 kPa, a compressive strain rate of 21.4%, an initial conductivity of 0.58 S / cm, a resistance change rate of 93.5% when the compressive strain is 10%, and a sensitivity coefficient of 9.35. It has good mechanical properties and pressure sensing performance.
[0075] Example 4
[0076] The difference between this embodiment and embodiment 1 is that the amount of graphene nanosheets added in step S1 is 1.5wt% of the PDMS primer, and the other operations are the same as those in embodiment 1.
[0077] After testing, the three-dimensional porous conductive polymer composite material prepared in this embodiment has a compressive strength of 36.52 kPa, a compressive strain rate of 17%, an initial conductivity of 0.81 S / cm, a resistance change rate of 79% when the compressive strain is 10%, and a sensitivity coefficient of 7.9. It has certain mechanical properties and pressure sensing function.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that the amount of graphene nanosheets added in step S1 is 3.5wt% of the PDMS primer, and the other operations are the same as those in Example 1.
[0080] After testing, the compressive strength of the material prepared in this comparative example is 48.69 kPa, the compressive strain rate is 8%, and the initial conductivity is 1.1 S / cm; when the compressive strain is 5%, the resistance change rate is 40% and the sensitivity coefficient is 8, but the resistance change response range is too narrow to be used for actual press sensing applications.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that multi-step heat treatment is not adopted in step S2, the temperature treatment process is selected as heating at 120° C. for 480 minutes, and the other operations are the same as those in Example 1.
[0083] After testing, it was found that the material prepared in this embodiment had structural collapse after the drying operation was completed, and had no mechanical and pressure sensing capabilities.
[0084] Comparative Example 3
[0085] The difference between this comparative example and Example 1 is that in step S1, the graphene nanosheets are replaced with carbon nanotubes, the filling amount is selected to be 0.5 wt %, and the other operations are the same as those in Example 1.
[0086] After testing, the compressive strength of the material prepared in this embodiment is 29.67 kPa, the compressive strain rate is 23%, and the mechanical properties are good. However, the intrinsic conductivity of carbon nanotubes is small, so the initial conductivity of the porous three-dimensional conductive composite material prepared is only 0.05 S / cm. When the compressive strain is 10%, the resistance change rate is 12%, and the sensitivity coefficient is only 1.2, which cannot be used for actual pressure sensing applications.
[0087] The test results of the embodiments and comparative examples are shown in Tables 1 and Figure 5-Figure 12 .
[0088] Table 1 Test results of embodiments and comparative examples
[0089]
[0090]
[0091] Comparing Example 1 and Example 2, when the type of solvent for dispersing graphene nanosheets is changed, the performance of the three-dimensional porous conductive polymer composite material prepared by 3D printing is slightly affected. It is speculated that the boiling point of the acetone solvent is lower than that of the tetrahydrofuran used in Example 1, and the solvent evaporates earlier during heat treatment, which has a slight effect on the performance.
[0092] Comparing Example 1 and Example 3, when the amount of precursor increases, this indicates that increasing the amount of PDMS can increase the compressive strength and compressive strain rate of the material.
[0093] Comparing Example 1 with Example 4 and Comparative Example 1, as the amount of graphene nanosheets increases, the electrical conductivity increases and at the same time, the two-dimensional structural characteristics of graphene increase the compressive strength of the three-dimensional porous conductive polymer composite material, which correspondingly leads to a significant decrease in its compressive strain rate; when the added amount exceeds a certain level, the three-dimensional porous conductive polymer composite material cannot be used as a pressure sensor.
[0094] Comparing Example 1 and Comparative Example 2, a porous resilient material cannot be obtained by using a one-step temperature treatment. It is speculated that during the one-step heat treatment, due to the high temperature, deionized water and cyclohexane evaporate together, but PDMS has not solidified in time, making the material structure difficult to support and causing collapse.
[0095] Comparison of the results of Example 1 and Comparative Example 3 shows that graphene cannot be replaced by other nanomaterials such as carbon nanotubes, carbon nanohorns, carbon black, and carbon nanoonions. This is because graphene nanosheets are two-dimensional sheet structures, which play a good supporting role after being filled in a polymer matrix. Carbon nanotubes are linear structures, while carbon nanohorns, carbon black, and carbon nanoonions are granular structures and have no supporting role. Therefore, after adding fillers such as carbon nanotubes and carbon black, the shape of the final product will collapse and will not have compressibility.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. A 3D printing ink, characterized in that: It is composed of the following components in parts by weight: 0.175-1.2 parts of graphene nanosheets, 35-40 parts of polydimethylsiloxane, 10-15 parts of cyclohexane, 45-50 parts of deionized water, and 3.5-4 parts of curing agent.
2. The 3D printing ink according to claim 1, characterized in that: Prepared by the following method: Ultrasonic dispersion of graphene nanosheets in a solvent forms a graphene dispersion, polydimethylsiloxane is added to the graphene dispersion and mechanically stirred and dispersed to obtain a mixed solution, the mixed solution is placed on a heating table, and the solvent is evaporated at 70-80° C. to obtain a precursor; the filling amount of the graphene nanosheets is 0.5-3wt% of the polydimethylsiloxane; The precursor, cyclohexane and deionized water are mixed in a weight ratio of (35-40%): (10-15%): (45-50%); a curing agent of 10% by weight of polydimethylsiloxane is added during the mechanical stirring and blending process to obtain a 3D printing ink.
3. The 3D printing ink according to claim 2, characterized in that: The solvent is one of tetrahydrofuran, chloroform and dichloromethane; 1g of graphene nanosheets is dispersed in 15-20ml of the solvent.
4. The 3D printing ink according to claim 2, characterized in that: Ultrasonic dispersion was performed for 10-15 min, with an ultrasonic power of 750 W and a frequency of 50 Hz; the solvent was evaporated at 70°C on a heating table.
5. A three-dimensional porous conductive polymer composite material prepared by 3D printing, characterized in that: Prepared by the following method: A 3D printer is used to print the 3D printing ink according to any one of claims 1 to 4 according to a predetermined structure to obtain a precursor material, and the precursor material is subjected to five-stage heat treatment to obtain a three-dimensional porous conductive polymer composite material.
6. The three-dimensional porous conductive polymer composite material prepared by 3D printing according to claim 5, characterized in that: The five-stage heat treatment process is: (1) Heating at 48-52°C for 30 minutes; (2) heating at 88-92°C for 60 minutes; (3) heating at 98-102°C for 90 minutes; (4) heating at 118-122°C for 120 minutes; (5) Heating at 138-142°C for 360 minutes.
7. The three-dimensional porous conductive polymer composite material prepared by 3D printing according to claim 5, characterized in that: The five-stage heat treatment is carried out in an oven at normal pressure, and the oven heating rate is 1-5°C / min.
8. The three-dimensional porous conductive polymer composite material prepared by 3D printing according to claim 5, characterized in that: The three-dimensional porous conductive polymer composite material is in the shape of an elongated strip, with a thickness of 1.8 to 2.0 mm in a naturally stretched state, and its length and width can be adjusted as needed; the three-dimensional porous conductive polymer composite material has a compression strength of 30 to 40 kPa, a compression strain rate of 17 to 22%, and an initial conductivity of 0.56 to 0.58 S / cm; when the compression strain is 10%, the resistance change rate is above 75%.
9. The three-dimensional porous conductive polymer composite material prepared by 3D printing according to claim 5, characterized in that: The air pressure on the printing nozzle is 0.1-0.3 MPa, the moving speed of the printing nozzle is 5 mm / s, the diameter of the printing nozzle is 0.2 mm, the spacing between the single filaments in the layer is 0.1 mm, and the layer thickness is 0.2 mm.
10. Use of the three-dimensional porous conductive polymer composite material prepared by 3D printing as claimed in claim 5 in a piezoresistive sensor.